Understanding the link between inter-group relations and psychological issues - Jamsari Hashim; Romzi Ationg; Mohd. Sohaimi Esa (Secholian Publication, 2021)
Understanding the relationship between inter-group relations, stress and copying strategies will continue to be an integral part of modern society. However, many still tend to misunderstood about the impact of intergroup relations towards stress. Apart from that, many still lacking in understating how to deal with stress caused by inter-group relations. For this reason, explaining the significant of inter-group relations in people’s stress and the way the people should deal with stress caused by inter-group relations is immensely valuable. This paper presents a discussion on the relationship between inter-group relations, stress and the way the people should deal with stress caused by inter-group relations. It is hoped that the paper provides room for improved knowledge and understanding on the relationship between inter-group relations and stress, and the way they should be dealt with stress caused by inter-group relations.